2021
DOI: 10.1142/9789814713955_0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Contents Design in Mathematical Inquiry in High School Textbooks

Abstract: Ahanjideh, Akbari, Fakharan and Trevisan proposed a conjecture on the distribution of the Laplacian eigenvalues of graphs: for any connected graph of order n with diameter d ≥ 2 that is not a path, the number of Laplacian eigenvalues in the interval [n − d + 2, n] is at most n − d. We show that the conjecture is true and provide a family of graphs to show that the bound is best possible. This establishes an interesting relation between the spectral and classical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 264 publications
(475 reference statements)
0
2
0
Order By: Relevance
“…Speaking of the large-size Chinese classes, scholars have shown interest in the curriculum design. A recent study revealed that compared with the U.S., the mathematics curriculum in China is more enriched in knowledge points, more specific in standard demands, deeper in terms of difficulty, and better sequenced according to the advancement of grades [10].…”
Section: Review Of the Literature On The Paradox Of Chinese Learnersmentioning
confidence: 99%
“…Speaking of the large-size Chinese classes, scholars have shown interest in the curriculum design. A recent study revealed that compared with the U.S., the mathematics curriculum in China is more enriched in knowledge points, more specific in standard demands, deeper in terms of difficulty, and better sequenced according to the advancement of grades [10].…”
Section: Review Of the Literature On The Paradox Of Chinese Learnersmentioning
confidence: 99%
“…Due to the high height and weight values of the ore pass undergoing ore release, the easy destabilization during release, and the fixed iron support of the ore pass release simulator, the simulation of the ore pass acrylic tube constitutes a triangular cone structure and can guarantee the stability of the model when filled with ore. The whole triangular cone is stable when the three corners of the cone bottom provide a support force with the same direction of target and similar strength 30 . The inclination angle is calculated by the equation tan α = S/L(α denotes the angle of inclination of the ore pass, S denotes the vertical height from the connection of the bracket and the ore pass tube to the bottom of the base, and L denotes the distance between the point of vertical projection of the connection of the bracket and the ore pass tube to the base and the pivot point where the base and the ore pass tube are connected.…”
Section: Similar Simulation Experiments Of Mine Release From the Ore ...mentioning
confidence: 99%